Role of digitalized sustainable manufacturing in SME’S: a bibliometric analysis - Sankar, Kiran; Gupta, Sumit; Luthra, Sunil; Jagtap, Sandeep (Elsevier, 2026)
The evolution of digital manufacturing is inherently linked with Computer Integrated Manufacturing (CIM) since 1980. CIM triggers the partial or fully automation in the industrial sector. Due to the global competitiveness and mandatory requirement of triple bottom line sustainability approach, the industries are on the verge of adapting digitalized sustainable manufacturing. The Digital manufacturing encompasses the whole integration throughout product life cycle and process, real-time monitoring of entire system, adaption of new innovative technologies in the context of sustainability. Nevertheless, DM is not restricted to a specific area, it includes all the tools and technologies for the quality improvement, customization, and efficient production strategies. The I4.0 technologies are vital elements of the Digital manufacturing paving the way to the sustainability. DM is the culmination of all information and communication technologies with high-speed computation capability, real-time data analysis by AI technology and finally cluster of all innovative technologies. Mostly all large-scale industrial sectors are adapting the digital technologies for existence survival in the international market. But the scenario of SME’S is contradictory, as they are perplexed in financial return, and ambiguous about the impact of these technologies on the accomplishment of overall sustainability. Especially, the adaption of innovative technologies in context of overall sustainability will cause a huge economic burden on the SME’S due to lack of funds and resources, and They must be reinforced by the government legislations and full back support from all corners. However, the past academic research was focused on the economic benefits of the digitalization and seldom efforts on providing insights about the integration of digitalization with triple bottom line sustainability. In addition, they envisioned the profitable aspects of the digital technologies in large scale manufacturing sector. These research gaps had been explored in the current study. The paper aims to conduct a bibliometric analysis on the past research developments in the digitalized sustainable manufacturing enhanced by the visualization software VOS in SME’S for providing a clear insight into the strategies, impediments, and ongoing trend in the small-scale sector.
Part of special issue: International Conference on Advanced Research in Industrial & Manufacturing Applications, Edited by Amar Patnaik, Devkumar S. Callychurn, G S Dangayach, Tej Singh
Keywords: Digital manufacturing; Sustainability; Digitalized sustainable manufacturing; Innovation